2009
DOI: 10.7498/aps.58.1105
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Cherenkov source with modified photonic band-gap cells

Abstract: A relativistic Cherenkov source with slow wave system consisting of modified photonic band-gap cells is proposed and investigated. The high frequency structure simulator and three-dimensional particle-in-cell simulation code are used to study the dispersion characteristic of TM01-like mode and the interaction between electromagnetic wave and electron beam. The results show that, in the slow wave system with modified photonic band-gap cells, the TM01-like mode has much better azimuthal symmetry, the non-axisymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[3−9] In Ref. [10], a slow-wave structure (SWS) consisting of modified PBG structures and metal plates is employed to suppress the competition modes in a Ka-band relativistic Cherenkov source. The PIC (particle-in-cell) simulation results have demonstrated that the SWS operates on in TM 01 -like mode and has good mode selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[3−9] In Ref. [10], a slow-wave structure (SWS) consisting of modified PBG structures and metal plates is employed to suppress the competition modes in a Ka-band relativistic Cherenkov source. The PIC (particle-in-cell) simulation results have demonstrated that the SWS operates on in TM 01 -like mode and has good mode selectivity.…”
Section: Introductionmentioning
confidence: 99%